Influence of processing parameters on the surface quality of electrophoretically deposited alumina coatings on foam ceramics. Issue 13 (October 2022) - Voigt, Claudia; Endler, Dirk; Dietze, Christin; Hubálková, Jana; Moritz, Kirsten; Aneziris, Christos G.
Abstract: Previous work showed that the electrophoretic deposition of coatings with aligned pore channels is technically feasible on Al2 O3 -C foams. In the next step, the amount and size of cracks in the sintered coatings should be reduced. The study revealed the drying conditions, alumina raw materials used, the chemistry of the foam skeleton and the sintering conditions as significant influences. The best drying procedure was freeze drying after sudden freezing in liquid nitrogen. Three alumina raw materials with different particle size distributions were tested with regard to linear shrinkage, number of cracks and number of channel-like pores. The CT 9 and CL 370 showed a low number of cracks, however CT 9 possessed almost no pores. The Al2 O3 -C foam skeletons electrophoretically coated with CL 370 and sintered at 1600 °C in air showed the best results with a low number of small cracks and high number of channel-like pores. Graphical Abstract: ga1